Software process certification: A practical model for maintaining software quality - Baharom, Fauziah; Yahaya, Jamaiah H.; Deraman, Aziz; Hamdan, Abdul Razak (Inderscience Enterprises Ltd., 2013)
Software quality issues are considered as important and critical due to the uncertainties situation among stakeholders, users and suppliers to guarantee and assure the status of the software products.Previous studies have indicated that some software organizations did not adopt and practice any development standards during software development and their products seemed to face quality problems throughout its life cycle. At the same time, users claim that software quality is not getting improved but deteriorated steadily and worsening.This situation indicates that there is still lack of mechanism for monitoring and ensuring the quality status of the software products and third party assessment and certification are one option to solve this uncertainty.A new model for software certification named as Software Process Assessment and Certification (SPAC) was developed that emphasizes on five main factors: the quality of process, the quality of people, the use of development technology, the quality of working environment and project constraints.The factors were identified through the state of theory and practices.The practicality of the SPAC model was validated through collaboration with industries in Malaysia via case study.The result of the case study indicates that the proposed model is feasible and practical in the real working environment.